Patara, Türkei. Epigraphische Feldforschung. Die Arbeiten der Jahre 2016 bis 2018 - Schuler, Christof (e-Forschungsberichte des DAI, 2018)
Patara in Lycia (south-western Turkey) was one of the leading cities of the region and a harbour of major importance in the eastern Mediterranean. Since 1988 systematic excavations conducted by a team of Akdeniz University Antalya have brought to light a wealth of information about the previously unexplored city. Ca. 650 new inscriptions have created a completely new foundation for the history of the city and the whole region. A joint team of the Commission for Ancient History and Epigraphy of the DAI and Münster University is working towards a new corpus of the inscriptions of Patara which will present the texts with detailed historical commentaries.